ANALISIS PENGARUH WORD OF MOUTH, LOKASI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Survei Konsumen pada Warung Soto Seger Mbok Giyem di Boyolali) - Alwi Suddin, Rudi Effendi, Marjam Desma Rahadhini & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze: 1) the effect of entrepreneurial characteristics on student’s entrepreneurship intentions 2) the effect of entrepreneurship motivation on student’s entrepreneurship intention, and 3) the effect of entrepreneurial characteristics on student’s entrepreneurship intenton with on the entrepreneurship motivation as a moderating variable. This study is a survey. The study population were students of the Faculty of Economics Slamet Riyadi University Surakarta in years 2012 and 2013. The research sample 59 used purposive sampling then used proportional cluster random sampling technique. The technique of collecting data used interviews, questionnaires and observations. Data were analyzed using the research instrument test, classic assumption test, multiple linear regression analysis, t-test, F, coefficient determination and test the absolute difference. The results showed that entrepreneurial characteristics has significant effect on student’s entrepreneurship intention. Entrepreneurship motivation has significant effect in studentsinfluence the entrepreneurship intention. Entrepreneurship motivation does not moderate effect of on entrepreneurial characteristics on student’s entrepreneurshipintention.Keywords: entrepreneurial characteristics, entrepreneurship motivation and entrepreneurship intention.